Transparent of temporo-mandibular disorder case with progressive deafness and vertigo - Fandialan, Lolita Flores
This article deals with a patient who suffered from edema of the eustachian tube for 1 year, which led to progressive deafness, and vertigo. Along with these, she had tight jaw and pain especially in the morning, shoulder pain, back and numbness of the arms. There was no positive finding in otolaryngologic, neurologic and EENT examinations. It has been found that a number of patients in this category have the TMJ disorder associated with spasms of the muscles of mastication as a consequence of lost natural teeth either in the anterior of posterior region wherein the mandible (condyle) has a potential to move up and back into the glenoid fossa.
Keywords: Vertigo; Temporo-mandibular dysfunction syndrome; Myofascial pain dysfunction; Cranio-mandibular somatic dysfunction